Predicted increased risk of squamous cell carcinoma induction associated with sunbed exposure habits. (26th May 2015) - Tierney, P.; de Gruijl, F.R.; Ibbotson, S.; Moseley, H.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Cumulative exposure to solar ultraviolet radiation (UVR) is a risk factor in the induction of squamous cell carcinoma (SCC). High‐output sunbeds emit significant levels of UVB radiation. Sunbeds in the U.K. emit UVR levels that exceed the European limits. What does this study add? This study uses published emission spectra from sunbeds to quantify the increased risk of SCC induction according to pattern of use and background sunlight exposure. By age 55 years, the risk of SCC induction from exposure to median UVR levels between the ages of 20 and 35 years from a sunbed is increased by 90%. A predictive, quantifiable relation is proposed between sunbed use, including the type of sunbed used, and SCC induction.